2004
DOI: 10.1007/s00125-004-1587-0
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes and risk of non-embolic ischaemic stroke in Japanese men and women

Abstract: Aims/hypothesis. The aim of this study was to examine the relationship between type 2 diabetes and risk of ischaemic stroke in Asian populations. Methods. We conducted a 17-year prospective cohort study in 10,582 Japanese individuals (4287 men and 6295 women) aged 40-69 years living in five communities in Japan. All subjects were free of stroke and CHD at baseline. Diabetes was defined as a fasting glucose level of ≥7.0 mmol/l, a non-fasting glucose of ≥11.1 mmol/l, or receiving medication for diabetes.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 19 publications
(31 reference statements)
4
74
2
1
Order By: Relevance
“…Several studies have recently assessed the relationship between type 2 diabetes and the risk of stroke. Type 2 diabetes has been shown to be an independent risk factor for stroke morbidity [15,[18][19][20][21][22] and mortality [14,16,17,22,40]. The Renfrew and Paisley Study found that type 2 diabetes was a predictor of stroke incidence among women but not among men [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have recently assessed the relationship between type 2 diabetes and the risk of stroke. Type 2 diabetes has been shown to be an independent risk factor for stroke morbidity [15,[18][19][20][21][22] and mortality [14,16,17,22,40]. The Renfrew and Paisley Study found that type 2 diabetes was a predictor of stroke incidence among women but not among men [41].…”
Section: Discussionmentioning
confidence: 99%
“…Several prospective studies have assessed the independent effect of type 2 diabetes on stroke risk, with inconsistent results. Some [14][15][16][17][18][19][20][21][22], but not all studies [23,24], have identified type 2 diabetes as an independent risk factor for stroke. Moreover, it is not fully understood whether the risk of stroke death associated with incident diabetes is similar to that associated with incident stroke.…”
mentioning
confidence: 99%
“…Since April 1975, this laboratory has been certified by the CDC-NHLBI Lipid Standardization Program of the Center for Disease Control and Prevention (Atlanta, GA, USA) [15]. Blood glucose levels were measured at this site using the cupric-neocuproine method [16] between 1975 and 1986 [17]. Because blood glucose levels are now widely measured with the hexokinase method, the serum glucose levels were adjusted by using a formula ([0.047×(glucose concentration in mg/dl)]−0.541) previously reported by the same laboratory, which gives levels in mmol/l [17].…”
Section: Methodsmentioning
confidence: 99%
“…Blood glucose levels were measured at this site using the cupric-neocuproine method [16] between 1975 and 1986 [17]. Because blood glucose levels are now widely measured with the hexokinase method, the serum glucose levels were adjusted by using a formula ([0.047×(glucose concentration in mg/dl)]−0.541) previously reported by the same laboratory, which gives levels in mmol/l [17]. Iso et al [17] reported that this formula was obtained from 60 random samples of blood with the regression line (r 2 =0.93).…”
Section: Methodsmentioning
confidence: 99%
“…In diabetic patients, the proportion of ischemic heart disease (IHD) is two‐ to fourfold higher3, the risk of stroke is approximately twofold greater4 and the risk of peripheral arterial disease (PAD) is approximately fourfold greater5 than in non‐diabetic patients. In Japan, DM was reported as a risk factor for cardiovascular disease and coronary heart disease6, and DM is related to coronary heart disease among women and ischemic stroke among both sexes7.…”
Section: Introductionmentioning
confidence: 99%